OSRA Grant Cycle 2 Public Reports : Project Title: Factors that influence Qatari Family Stability: Testing a Vulnerability and Resiliency Model - Abdrabo Soliman (10039181) (2019)
This abstract highlights the contemporary challenges faced by families, with a specific focus on the rising divorce rates in Qatar and Arab societies. Various reports and studies have documented this trend, reflecting the changing dynamics within families. Despite these challenges, families in these regions remain crucial as the primary social system, responsible for meeting the basic needs of its members and passing on cultural and religious values to new generations. The importance of understanding the family's role in these contexts is emphasized, as well as the need for societal support to ensure the family's stability and continued mission. As the family's stability is compromised, it may face significant problems, underscoring the importance of addressing these issues to maintain the well-being of families in Arab societies.